LINGUISTIC STRUCTURE IN THE PROPHETIC HAMZIA OF SHAWQI (Eureka Journal of Language, Culture & Social Change, 2026)
This research entitled (The Linguistic Structure in the Prophetic Hamziyah of Shawqi), deals with the linguistic structure at its different levels: phonetic, morphological, structural and semantic poem of the most important poems in praise of the Prophet, may God bless him and grant him peace, in the modern era, and the research has followed the descriptive analytical approach, and the research came out with some results, including: Shawqi committed to a traditional sea of poetry is the sea of full, the poet took advantage of the inner music to show his idea and emotion, including: Attention to the choice of the singular sound, and attention to the sound within the framework of the pronunciation, and Shawqi was interested in homogeneity between words because of the beautiful musical impact it leaves, and he also paid attention to repetition to confirm his idea. Within the framework of the morphological structure, we found the diversity of Shawqi's use of verb forms, sources and different derivatives with their general connotations and their own connotations in the poem. In the study of structural structure, we found synthetic phenomena such as advancement, delay, and objection with their rhetorical connotations. Within the framework of the semantic structure, five semantic fields emerged, including the field of words of happiness, the field of religious words, and the field of words of the Arab environment.
Keywords: Structure - sounds - morphology - structures – significance.